Understanding Teachers’ Attitudes Toward Inclusive Education Through Sentiment Analysis: A Case Study in Malang, Indonesia - Rifqah, Rifqah; Nurchalisa, Ade (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
While teachers’ roles in inclusive education are critical, research employing sentiment analysis to understand their experiences remains underexplored. This study investigates teachers’ attitudes and practices in managing inclusive classrooms at SMP Muhammadiyah 2 Malang. A qualitative case study was conducted using secondary data derived from previous semi-structured interview research, providing contextual insight without additional data collection. Thematic analysis was applied to identify recurring patterns of inclusive practices, complemented by automated sentiment analysis using a zero-shot BART-MNLI model to capture teachers’ evaluative tone. The findings reveal generally positive attitudes toward inclusion, reflecting empathy, flexibility, and commitment, though negative sentiments were also expressed in relation to systemic limitations. The study offers practical implications for teachers and policymakers, while also contributing methodologically through the integration of thematic and sentiment analysis.